SYNTHESIS OF 6-TERT-OCTYL AND 6,8-DITERT-BUTYL COUMARINS, TWO COUMARINS OF BIOLOGICAL INTEREST - Zárraga Olavarría, Miguel; Dahrouch, Mohamed; Lisboa, Esteban; Arroyo, Patricia; Miranda, Alberto (Journal of the Chilean Chemical Society, 2021)
In this study, the synthesis of new coumarins with aliphatic chains is discussed. The incorporation of the 6-tert-octyl and 6,8-ditert-butyl chains into a coumarin structure from alkylphenols, allows obtaining hydrophobic coumarins with good yields. These coumarins can be potential modulators of TRPV1 receptors. Synthesis and spectroscopic data of these new coumarins are analyzed.